2019
DOI: 10.1002/ffj.3559
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of chemical content, enzyme inhibitory propert, antioxidant and antibacterial activity of Aristolochia bodamae Dingler (develiotu) (Aristolochiaceae) root extracts from Samsun, Turkey

Abstract: The present work aimed to evaluate the phytochemical contents of the methanol (ME), ethanol (ET), water (W), acetone (AC), ethyl acetate (EA), and hexane (HE) of Aristolochia bodamae root (ABR) as well as inhibition potential, antioxidative, and antimicrobial activities. The chemical composition analysis and antioxidant activity of ABR extracts were performed by commonly used assays. Antibacterial activities of ABR extracts were tested against three gram‐positive and three gram‐negative bacteria using disk dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Which focused on the species A. clematitis L., it was shown that by means of a conventional extraction method and using 60% ethyl alcohol as solvent, the maximum amount of polyphenols recovered from this species was 11.04 mg caffeic acid/g dried plant (Benmehdi et al, 2017). In the case of Aristolochia bodamae Dingler, using the Soxhlet extraction method and the same type of solvent mentioned in the previous study, it was possible to obtain three times the amount of polyphenols, namely 31.11 mg GAE/g, compared to the value recorded for A. clematitis L. (Benmehdi et al, 2017;Ozen et al, 2019). Nile et al (2021) observed a variation in the total content of polyphenols depending on the parts of the C. majus L. plant, which ranged from 7.76 to 23.67 mg/g.…”
Section: Discussion Discussion Discussionmentioning
confidence: 62%
“…Which focused on the species A. clematitis L., it was shown that by means of a conventional extraction method and using 60% ethyl alcohol as solvent, the maximum amount of polyphenols recovered from this species was 11.04 mg caffeic acid/g dried plant (Benmehdi et al, 2017). In the case of Aristolochia bodamae Dingler, using the Soxhlet extraction method and the same type of solvent mentioned in the previous study, it was possible to obtain three times the amount of polyphenols, namely 31.11 mg GAE/g, compared to the value recorded for A. clematitis L. (Benmehdi et al, 2017;Ozen et al, 2019). Nile et al (2021) observed a variation in the total content of polyphenols depending on the parts of the C. majus L. plant, which ranged from 7.76 to 23.67 mg/g.…”
Section: Discussion Discussion Discussionmentioning
confidence: 62%
“…The results can be seen in Table and the chromatogram in Figure S1. These compounds have already had their antioxidant activities studied, which proves that these polyphenolic compounds have high potential as enzymatic inhibitors. Barbatimão is a promising species because it has a high concentration of polyphenols in the bark.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of traditional uses for species of the genus Aristolochia were found in the literature. Of the traditional uses cited, the most common uses are anticancer (33 articles) , antibacterial (31 articles) [23,25,29,30,38,39,45,49,, antioxidants (18 articles) [22,25,29,33,34,46,55,60,61,70,73,74,[77][78][79][80][81][82], snake anti-venom (13 articles) [21,22,39,40,76,[83][84][85][86][87][88][89][90], anti-inflammatory (11 articles) [22,40,46,47,74,86,[91][92][93][94]…”
Section: Ethnomedicinal Usementioning
confidence: 99%